بلاغية التقديم والتأخير في قصة "سفينة نوح" لأحمد شوق (دراسة تحليلية أسلوبية): Foregrounding and Backgrounding in the Story of Noah's Ark by Ahmed Shawqi (A Stylistic Analytical Study) - Zaid, Abdul Hafidz; Setiyadi, Alif Cahya; Putra, Alde Mulya; Anhar, Anhar (Diwan : Jurnal Bahasa dan Sastra Arab, 2023)
تعد القصة الشعرية "سفينة نوح" لأمير الشعراء أحمد شوقي من أحد الأشعار العربية المعاصرة ذات القيم الأدبية الرفيعة في تاريخ الفنون الأدبية العربية. وذلك لما فيها من العوامل التي تثير ملكة التصور ومما يغذي ملكة التفكير لدى القارئين والسامعين. ومن أهم العوامل الأسلوبية البليغة المستخدمة فيه هي بلاغة التقديم والتأخير التي تؤثر بوجه مباشر على معاني الأسلوب. فتهدف هذه المقالة إلى دراسة ظواهر التقديم والتأخير الموجودة في هذه القصة. ويكون التحليل فيها بالتحليل الأسلوبي الأدبي المعاصر بالمنهج الوصفي. وتنتج هذه الدراسة بأن هذه القصيدة تستخدم بلاغة التقديم والتأخير في أبياتها. وقد تشتمل على تقديم الظرف على الفعل والفاعل وعليهما معا، والمفعول على الفاعل، والحال، وشبه الجملة جر ومجروره وتقديم اسم كان على خبره وتأخيره عليه. وقد يكون في القصيدة ستة مواضع لتقديم الظرف على الفعل والفاعل وعليهما معا وأربعة مواضع في تقديم المفعول على الفاعل وخمسة مواضع في تقديم شبه الجملة وثلاثة مواضع لتقديم اسم كان وتأخيره وموضعين في تقديم الحال. Abstract "Noah's Ark," considered one of Prince of Poets Ahmed Shawqi's high-level literary masterpieces, holds significant influence on reader and audience apprehension and imagination within the Arabic tradition. Its key characteristic lies in the unique poetic style, particularly in the foregrounding and backgrounding of words that carry semantic implications. This study aims to analyze the stylistic phenomena within the story. Utilizing a primarily descriptive approach with a focus on contemporary stylistic analysis methods, the study reveals the presence of foregrounding and backgrounding techniques. These techniques involve foregrounding and backgrounding of adverbs of place and time, Emphasis on objects over subjects, foregrounding of circumstantial clauses ("jar wa majrur"), foregrounding and backgrounding of "kana" nouns and their predicates. The study identifies six instances of foregrounding for adverbs of place and time, three instances for both "kana" nouns and circumstantial clauses, five instances for clauses, and four instances for object over subject foregrounding.